2020
DOI: 10.3390/ijerph17165663
|View full text |Cite
|
Sign up to set email alerts
|

Exploring WHO Communication during the COVID 19 Pandemic through the WHO Website Based on W3C Guidelines: Accessible for All?

Abstract: Health crisis situations generate greater attention and dependence on reliable and truthful information from citizens, especially from those organisations that represent authority on the subject, such as the World Health Organization (WHO). In times of global pandemics such as COVID-19, the WHO message “health for all” takes on great communicative importance, especially from the point of view of the prevention of the disease and recommendations for action. Therefore, any communication must be understandable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Table 1 shows how the papers that were analysed are distributed by publication type and source, by geographical focus, and by the health conditions or impairments addressed. [110,111] Ecological study 1 (1.2%) [112] Survey research, with qualitative analysis 1 (1.2%) [31] Quantitative analysis of contacts to support services 1 (1.2%) [113] Analysis of webpages on accessibility compliance 1 (1.2%) [114] Documentary research and framework analysis 1 (1.2%) [115] Country case report 1(1.2%) [116] Empirical studies (peer-…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows how the papers that were analysed are distributed by publication type and source, by geographical focus, and by the health conditions or impairments addressed. [110,111] Ecological study 1 (1.2%) [112] Survey research, with qualitative analysis 1 (1.2%) [31] Quantitative analysis of contacts to support services 1 (1.2%) [113] Analysis of webpages on accessibility compliance 1 (1.2%) [114] Documentary research and framework analysis 1 (1.2%) [115] Country case report 1(1.2%) [116] Empirical studies (peer-…”
Section: Resultsmentioning
confidence: 99%
“…The current COVID-19 crisis could be seen as a so-called "black swan moment" with regard to the training of health professionals and the need to examine the role of e-learning in particular [10][11][12]. The experience of OpenWHO in responding at scale and pace to the urgent need for high-quality and accessible web-based learning for COVID-19 has clearly and consistently demonstrated that the positive effects of digital learning are diverse and multiple and are relevant to many other spheres of a learners' life and work.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…For instance, an audit of press conferences in LMICs showed that only 65% of countries have used a sign language interpreter, with figures varying from 33% to 88% [ 74 ]. Globally, another analysis showed that pages of the World Health Organization’s website, March–May 2020, were only 60% compliant regarding web accessibility guidelines [ 75 ]. Additionally, people with sensory processing and visual impairments may need to rely or depend on touch and tactile senses for stimulus or to perform their routine activities or outdoor movement, and thereby face greater infection risks [ 33 , 38 , 40 , 43 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lack of accessible information (e.g., in press conferences, public health websites) was another modifiable environmental factor identified as a barrier to health equity for people with disabilities. This can be addressed with the straight application of existing guidelines, e.g., web-accessibility guidelines [ 75 ], the presence of sign language interpreters, and the use of transparent masks for the transmission of key public health information. Principles of health literacy [ 81 ] might also be useful for optimizing the access to and understanding of the needed preventive measures, for example, but not limited to, among people with developmental, intellectual, or cognitive impairments, as well as their caregivers.…”
Section: Discussionmentioning
confidence: 99%